The CRC Encyclopedi a of Mathematics. Vol. 1, 2 & 3 - Eric W. Weisstein (CRC Press, 2009)
This third edition of a bestseller is now presented as a three-volume set, making it much more accessible and easier to use when searching for information. Maintaining the format that made its predecessors so popular, this edition has been extensively expanded, revised, and updated. It now contains nearly 12,000 entries. Each article provides definitions, formulas, illustrations, web links, bibliographic information, and facts from mathematics, the sciences, and engineering. Written by a single author, the encyclopedia is written in an informal style, making it accessible to anyone who has an interest in mathematics. The three-volume set is beautifully bound with much improved typesetting and format.